Magnetization transfer MRI of third trimester fetal brain: a pilot of gestational myelin imaging - Sadanand, Siddharth; Stobbe, Rob; van Mieghem, Tim; Shinar, Shiri; Krishnan, Pradeep; Miller, Elka; Stanisz, Greg; Sussman, Dafna (Frontiers in Pediatrics, 2025)
BackgroundMagnetic resonance imaging (MRI) is commonly used as a tool for confirming a fetal brain abnormality suspected on ultrasound. Common clinical MRI sequences typically only reveal changes in the brain once there are gross abnormalities. Detection of more minute changes in brain tissue microstructure could permit earlier detection of complications, allowing for potentially more timely, effective interventions. Tissue microstructure corresponding to neuronal development can be captured before the appearance of broad anatomical changes using more advanced imaging, such as magnetization transfer (MT) MRI. This study aimed to investigate the feasibility of an MT MRI pulse sequence developed by the researcher, yarnball (YB) MT, for fetal brain imaging.MethodsA yarnball (YB) readout trajectory was used to accelerate imaging and increase sensitivity. A multiband saturation pulse was implemented to increase MT specificity from saturation transfer (ST) confounds. MT-weighted images were derived from three-point magnetization transfer ratio asymmetry (MTRasym) to reduce acquisition time to within a breath hold. Sensitivity and specificity were evaluated on agar phantoms with varied MT and ST confound concentrations. Pilot imaging was done with singleton third trimester gestations complicated with mild ventriculomegaly recruited from Mount Sinai Hospital.ResultsYB MT covers a 350 mm 3D field of view (FoV) within a 13 s breath hold and a 28 s acquisition. The sequence demonstrated a limit of quantification (LOQ) of agar of 0.62% w/w and no dependence on glucose in agar phantoms with glucose ST confound. Pilot imaging in vivo of third trimester pregnancies with mild ventriculomegaly with the sequence revealed MT contrast in the fetal brain that was spatially consistent with the development of white matter at this gestational age. All participants reported the sequence and the breath hold to be tolerable.ConclusionThe developed YB MT pulse sequence is sensitive to fetal physiological MT signal is tolerable to participants, and does not demonstrate sensitivity to ST confounds in phantom imaging. While the breath hold was reported to be tolerable, motion artefacts and spiral trajectory blurring affected subjects' imaging. Ongoing work, including online reconstruction, expedited trajectories, and improvements in the signal-to-noise ratio should address these challenges. This proof of principle is a step towards the clinical translation of gestational metabolic imaging, such as MT imaging of fetal myelin, for the early detection of gestational complications.